Planktonic foraminifera and sea-level changes in the upper Cretaceous of the Gurpi Formation, Lorestan basin, SW Iran. (February 2018) - Darabi, Ghamarnaz; Moghaddam, Iraj Maghfouri; Sadeghi, Abbas; Yusefi, Bijan
Abstract: The Gurpi Formation, one of the geological units of the Zagros Basin, stretches with in the Folded Zagros in the provinces of Khuzestan, Lorestan, and Fars, in southwest Iran. In total 490 samples were collected from the three sections to document the planktonic foraminifera. Overall, 58 species from 23 Planktonic foraminifera genera were recognized in this study. From a biochronostratigraphic point of view, 7 biozones were identified. Also, the age of Gurpi Formation in three sections were determined based on the identified biozones of early Campanian to late Maastrichtian. A depth of over 450–600 m has been designated for of the formation based on determine percentage planktonic in the total foraminiferal association (%P*) and the regression equation Depth = e (3.58718+(0.03534 × %P∗)) . Graphical abstract: Highlights: Based on the stratigraphic distribution of the well known foraminifers, seven biozones have established. The age of Gurpi Formation are determined based on identified biozones of Early Campanian to Late Maastrichtian. Low and rise percentage morphothype 3 of planktonic foraminifera thatreflected a low and a rise depth water.